Managing recent hot money inflows in Asia - Robert McCauley (Asian Development Bank Institute (ADBI), 2008)
This paper surveys the nature of capital inflows into Asia since the peak of the US dollar in the first quarter of 2002 and the policy responses to them. Portfolio equity flows have become more volatile and more responsive to global equity market developments. Inflows into local bond markets have become important, although they are often immeasurable, virtual investments through derivative instruments. In the market that shows the highest level of direct non-resident holdings, namely that of Indonesia, these seem quite sensitive to global equity volatility. The most important qualitative change over this period involved bank flows. In particular, foreign bank flows have returned to net inflows after five years of paydown after the 1997-98 financial crisis. Carry trades, although difficult to measure, appear to have become important, with notable growth in transactions in which a long position in one regional currency is taken against a short position in another one. Carry trades also show great sensitivity to global equity volatility. In the face of such increasingly volatile capital inflows, the authorities in the region have adopted both measures to encourage outflows and to discourage inflows. Outside of Korea, measures to encourage outflows have met with limited response owing to expectations of further strength in the domestic currency and, until recently, buoyant domestic equity markets. Some of the measures to discourage inflows have taken the form of making previous measures to discourage outflows more symmetric, while others have taken the form of reinstating much reduced or eliminated restrictions, while other have taken the form of new adaptations. These limits on capital inflows can be quite effective, but they set back the development of financial markets and clash with ambitions for internationalized currencies in the region.
Keywords: F21; F31; F32; F36; G12; 330; Kapitalimport; Kapitalverkehrspolitik; Asien